"Like you can tell a river where to go": Floods, ecological formations, and storied pedagogies of place. Issue 2 (15th March 2022) - Scherrer, Benjamin D.
Abstract: What emerges when climate-related displacement is positioned in conversation within the relational practices of collective resistance and oral tradition? In this article, I consider climate displacement and community placement through multiple layers within present day ecologies, narrative texts, and longer views of time. Situated within Black ecologies, I apply both archival stories and current research to think beyond plantation logics, with river ecosystems and wetlands, extending concepts of climate change education. The article is layered in place and time through the writing of Louisiana author Ernest Gaines, centering Black epistemologies, oral traditions, and storied pedagogies of place. Relating the ecological roles and intimacies of water in and beyond the colonizing US settler state might unsettle current universalized notions of displacement and climate change education.